2021
DOI: 10.1002/nafm.10625
|View full text |Cite
|
Sign up to set email alerts
|

Relating American Eel Abundance to Environmental DNA Concentration in the Bronx River

Abstract: The American Eel Anguilla rostrata has experienced a marked population decline due to a multitude of threats, including pollution, overfishing, and damming. Government agencies responsible for American Eel management have identified gaps in survey coverage and understanding of habitat needs as critical obstacles to recovery. However, efforts to expand American Eel monitoring are hindered by this species’ resistance to capture, the wide variety of habitats in which they occur, and their extensive natural range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
8
2
Order By: Relevance
“…eDNA concentrations explained 57% of the variation in estimated aquatic species abundance in 25 studies conducted in natural waters (Yates et al, 2019). For anguillid eels, studies have reported low (32%, Japanese eel, Itakura et al, 2019), variable (43%–95%, European eel, Weldon et al, 2020) and high (99%, American eel, Chin et al, 2021) explained variation of abundance estimates. Models that treat eDNA release as an allometric function of body size increase explained variation (Yates, Glaser, et al, 2021).…”
Section: Novel Ideas and Underutilised Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…eDNA concentrations explained 57% of the variation in estimated aquatic species abundance in 25 studies conducted in natural waters (Yates et al, 2019). For anguillid eels, studies have reported low (32%, Japanese eel, Itakura et al, 2019), variable (43%–95%, European eel, Weldon et al, 2020) and high (99%, American eel, Chin et al, 2021) explained variation of abundance estimates. Models that treat eDNA release as an allometric function of body size increase explained variation (Yates, Glaser, et al, 2021).…”
Section: Novel Ideas and Underutilised Resourcesmentioning
confidence: 99%
“…qPCR detects eDNA of targeted species with greater sensitivity and also measures its concentration (Kasai et al, 2021). Measured eDNA concentrations can be used to predict organism abundance by calculating their relation to populations estimated by independent methods (Chin et al, 2021). The inability of eDNA concentrations to fully explain the variance of independent population estimates is attributed to factors, other than organism abundance, that affect eDNA concentrations (notably variable rates of eDNA release, degradation and dispersal) (Caza-Allard et al, 2022).…”
Section: Datamentioning
confidence: 99%
“…As well as spatial heterogeneity, fish biomass can be low in the environment and because eDNA concentrations are often positively related to fish biomass or abundance, eDNA concentration also may be relatively low (Chin et al, 2021;Itakura et al, 2019Itakura et al, , 2020Klymus et al, 2015;Thomson-Laing et al, 2021;Weldon et al, 2020). In this study, irrespective of the extraction method used, the concentration of fish sedDNA was low for all sediment types and fish species analysed.…”
Section: Sediment Mass For Fish Sedimentary Dna Extractionmentioning
confidence: 51%
“…Heterogeneity in fish DNA is not only a feature of sedDNA, but also of water eDNA, highlighting a challenge of using eDNA approaches to detect fish (Baldigo et al, 2017; Buxton et al, 2018; Eichmiller et al, 2014; Shaw et al, 2016; Turner et al, 2015). As well as spatial heterogeneity, fish biomass can be low in the environment and because eDNA concentrations are often positively related to fish biomass or abundance, eDNA concentration also may be relatively low (Chin et al, 2021; Itakura et al, 2019, 2020; Klymus et al, 2015; Thomson‐Laing et al, 2021; Weldon et al, 2020). In this study, irrespective of the extraction method used, the concentration of fish sedDNA was low for all sediment types and fish species analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, point or transect‐based electrofishing strategies (Reid, 2011) are used by a variety of American Eel monitoring programs (e.g., Laffaille et al, 2005; Newhard et al, 2021); however, American Eels have been shown to be highly susceptible to injury from these methods (Reynolds & Holliman, 2004). Recently Cairns et al (2022) highlighted the importance of eDNA for American Eel monitoring and Chin et al (2021) showed that American Eel eDNA concentration can be used to predict abundance; however, there is still no validated eDNA assay for this organism. Therefore, the goal of our study was to develop and validate two eDNA assays for the American Eel that could serve as a noninvasive method to aid in conservation efforts of the species (e.g., determination of fish passage and reintroduction success).…”
Section: Introductionmentioning
confidence: 99%